2015
DOI: 10.16965/ijar.2015.232
|View full text |Cite
|
Sign up to set email alerts
|

Bony Suprascapular Foramen, a Potential Site for Suprascapular Nerve Entrapment: A Morphological Study on Dried Human Scapulae

Abstract: The superior transverse scapular ligament (STSL) is present above the suprascapular notch. It joins the two superior corners of this notch and converts it into suprascapular foramen through which passes the suprascapular nerve , while the suprascapular artery and vein usually pass above the ligament. The anterior coracoscapular ligament (ACSL) runs in the suprascapular notch, below the superior transverse scapular ligament. Narrowed bony foramen by ossification of STSL and ACSL is one of the predisposing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Whereas Jawed 18 and Mistry 19 recorded higher incidence and shiksha 20 , polguj 21 , and Soni 10 recorded a lower incidence. Hence the present study is in accordance with the study done by Udayasree and Usha.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas Jawed 18 and Mistry 19 recorded higher incidence and shiksha 20 , polguj 21 , and Soni 10 recorded a lower incidence. Hence the present study is in accordance with the study done by Udayasree and Usha.…”
Section: Discussionmentioning
confidence: 96%
“…It has been evident that anxiety is the common component on first exposure of the students to the cadaver; however, repeated exposures and pre-session induction by showing dissection videos and pictures facilitate in allaying the element of anxiety [ 49 - 50 ]. Due to the cost and effectiveness, formalin remained the main fixative for cadavers used in Indian medical schools; however, it has been recommended to create awareness among staff members and students about the usage and preventive measure [ 51 ]. In this study, similar findings have been observed that the repulsion from dissection is due to formalin and safety factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies on the ossified transverse scapular ligament have been done. In a study by Shiksha Jangde 6 (2015) incidence of complete ossification was 4.1% of the bones studied. In a study by Sachin Patil 7 (2019) the suprascapular ligament was ossified completely in 3.54% bones studied.…”
Section: Introductionmentioning
confidence: 95%